Instantaneous fuel consumption models of light duty vehicles and a case study on the fuel consumption at different traffic conditions in Metro Manila using Shepard's interpolation method - Abaya, Ernesto B. (Animo Repository, 2018)
The instantaneous fuel consumption measurements obtained from the chassis dynamometer tests using the drive cycles for light duty vehicles in Metro Manila was used in the development of speed-acceleration-fuel consumption models. The Shepard's interpolation method was used in the development of the models. A program C# language was used to execute the interpolation method.The resulting models are represented by speed-acceleration-fuel consumption surface graphs. The surface graph of each test vehicle represents its estimated fuel consumption variation according to its combined instantaneous speed and acceleration. Actual instantaneous speeds from speed data of surveyed vehicles, defining different traffic conditions by average speed, are used to interpolate instantaneous fuel consumption. Fuel economy, in terms of distance travelled (km) per volume of fuel consumed (liter), is computed from the totaled fuel consumption and total distance traversed. An increasing trend in fuel economy is observed when traffic conditions improve. © 2018 SAE International. All Rights Reserved.